2022
DOI: 10.3390/atmos13121990
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Two Severe Shamal Dust Storms and the Highest Dust Frequencies in the South and Southwest of Iran

Abstract: Dust storms create some of the most critical air quality problems in the world; the Middle East, located in the dust belt, suffers substantially from dust storms. Iran, as a country in the Middle East, is affected by dust storms from multiple internal and external sources that mostly originate from deserts in Iraq and Syria (especially the Mesopotamia region). To determine the highest dust loadings in the south and west of Iran, dust frequencies were investigated in the eight most polluted stations in the west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…All other parts of Iran present much lower wind speeds, which are generally increased along the Zagros and Alborz mountain ranges, since stronger winds occur at higher altitudes. The Iranian Plateau and coastal areas are characterized by rather weak winds, as well as the southwest part of Iran (Khuzestan Province), which is highly affected by Shamal dust storms mostly during the warm period of the year [108][109][110]. On an annual mean basis, the effect of "Qibla wind" [103] over the central Iranian Plateau seems to have a rather limited impact on the wind regime over the region.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…All other parts of Iran present much lower wind speeds, which are generally increased along the Zagros and Alborz mountain ranges, since stronger winds occur at higher altitudes. The Iranian Plateau and coastal areas are characterized by rather weak winds, as well as the southwest part of Iran (Khuzestan Province), which is highly affected by Shamal dust storms mostly during the warm period of the year [108][109][110]. On an annual mean basis, the effect of "Qibla wind" [103] over the central Iranian Plateau seems to have a rather limited impact on the wind regime over the region.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Thermal low-pressure systems over low topographic areas and the high-pressure Caspian Sea, along with intense surface winds over the dust sources caused the dust outbreaks and transport over Iran in summer [145]. Many dust storms in west, SW, and NW Iran were driven by the Shamal wind in summer [146] and frontal system in winter [147][148][149]. In other seasons, the east (Khorasan Province) and west (Western Azerbaijan Province; see [145]) of Iran were very often subject to the influence of ACAR air.…”
Section: Sitementioning
confidence: 99%
“…In the territory of Iran, the autumn contribution of ACAR-EL was quite uniform (0.03-0.05), while the impact of ACAR-TL was higher in the western and southern parts of the country (0.03-0.05) compared with the east and north of Iran (0.02-0.03). In addition, the authors of [146] showed dust storms mostly occurred from April to August and weakened after August in south, SW, and west of Iran. In addition, 84% of these areas were affected by dust storms from the Tigris-Euphrates plain in Iran and Syria, and internal dust sources had a smaller role in these hazards.…”
Section: Sitementioning
confidence: 99%
“…It includes investigation of (i) surface measured reported data, (ii) satellite remote sensing data and images, (iii) dust modeling, (iv) forward and backward trajectory analysis, and (v) synoptic analysis [32][33][34]. Methods were used in the dust studies in the Middle East region to investigate dust storm generation and transportation [35][36][37][38][39]. In some cases, soil properties and vegetation cover were investigated during the dust, along with meteorological parameters such as wind speed, wind direction, precipitation, air temperature, and so on [21,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…This factor had an important role in growing the frequency of dust storms in the Middle East region [43][44][45]. Also, dust storms are mainly categorized into two main groups: Shamal dust storms and frontal dust storms [35,39,[46][47][48], though haboob dust storms happen minimally in this region, too [49].…”
Section: Introductionmentioning
confidence: 99%